设随机变量X的分布律为P(X=k)=[img=11x33]1803b6910546dd2.jpg[/img](k=1,...6),则[img=29x17]1803b6910cda9be.jpg[/img]=
A: [img=52x54]1803b69115467b7.png[/img]
B: [img=18x43]1803b6911d907b5.png[/img]
C: 1
D: [img=18x43]1803b69124c31e8.png[/img]
A: [img=52x54]1803b69115467b7.png[/img]
B: [img=18x43]1803b6911d907b5.png[/img]
C: 1
D: [img=18x43]1803b69124c31e8.png[/img]
举一反三
- 设随机变量X的分布律为P(X=k)=[img=11x33]1803b6910546dd2.jpg[/img](k=1,...6),则[img=29x17]1803b6910cda9be.jpg[/img]= 未知类型:{'options': ['', '', '1', ''], 'type': 102}
- 设随机变量X与Y相互独立,X服从二项分布,n=2,p=0.5,Y服从参数为1的泊松分布,则P(X-Y=2)等于 A: [img=18x43]180306cf85e6127.png[/img] B: [img=18x43]180306cf8e7fc62.png[/img] C: [img=18x43]180306cf9672005.png[/img] D: [img=18x43]180306cf9eaa269.png[/img]
- 设随机变量X与Y相互独立,X服从二项分布,n=2,p=0.5,Y服从参数为1的泊松分布,则P(X-Y=2)等于 A: [img=18x43]1803837f58222da.png[/img] B: [img=18x43]1803837f606931d.png[/img] C: [img=18x43]1803837f6912dbc.png[/img] D: [img=18x43]1803837f7284cd5.png[/img]
- 设随机变量X与Y相互独立,X服从二项分布,n=2,p=0.5,Y服从参数为1的泊松分布,则P(X-Y=2)等于 A: [img=18x43]1803c47652894c3.png[/img] B: [img=18x43]1803c4765a76d6f.png[/img] C: [img=18x43]1803c47662939d4.png[/img] D: [img=18x43]1803c4766a514d6.png[/img]
- 设随机变量X与Y相互独立,X服从二项分布,n=2,p=0.5,Y服从参数为1的泊松分布,则P(X-Y=2)等于 A: [img=18x43]1802daeb8f72f27.png[/img] B: [img=18x43]1802daeb980955b.png[/img] C: [img=18x43]1802daeba092466.png[/img] D: [img=18x43]1802daeba885917.png[/img]